ຕະກອນໃນເຂດລຸ່ມແມ່ນໍ້າຂອງ - Pukinskis, Ilse (CGIAR Challenge Program on Water and Food, 2013)
Reviews current literature on Mekong sediments including: sources and volume, how sediments affect dams and reservoir, how much sediment will be blocked by dams, impact on riverine habitats, fisheries, agriculture, navigation, the Tonle Sap floodplains and the Vietnam delta, and if and how sediment losses can be mitigated.